O geoprocessamento como ferramenta para o estudo da fitofisionomia em propriedades rurais: um estudo de caso - Alonso, Mauricio (2011)
The study aimed to analyze the two farms of the central region of Mato Grosso - BR, on a scale of closest approach, identifying and diagnosing the existing reality. For this, we used geographic information system, compiling information from different sources and scales, in addition to data collection in the field, where based on scientific methods and literature review states, it was possible to identify the location. phytophysiognomy. The studies made possible a diagnosis of the areas studied, enabling a better understanding of their capabilities and needs to be adjusted to meet the legal assumptions and sustainability, as well as confirmed that the areas studied are located in the savana. The use of geographic information system - GIS, was efficient as a tool to aid analysis of regions with different sources of information and is recommended for diagnosis, planning and making decisions together supply chains, management and oversight.